Banjar Local Wisdom as a Dialectic in MI Arabic Language Teaching: A Comparative Analysis Between Formal Curriculum and Nusantara Islamic Values - Mahmudah Mahmudah; Muhammad Adli Nurul Ihsan; Hanna Nova Astuty (STAI Syaichona Moh. Cholil Bangkalan, 2026)
This study examines the dialectic between Banjar local wisdom and Arabic language pedagogy in Islamic Elementary Schools (MI) through the lens of Nusantara Islam. It addresses the critical tension between text-centric formal curricula and the sociocultural realities of students. Utilizing a Systematic Literature Review (SLR) and Comparative Meta-Synthesis, the research identifies that conventional, formalistic approaches often result in low student engagement and cultural detachment. Findings demonstrate that integrating Banjar values—such as papadah, pantun, and gotong royong—transforms Arabic instruction into a communicative, humanistic, and relevant process. The study culminates in the